2013
DOI: 10.1001/jamadermatol.2013.21
|View full text |Cite
|
Sign up to set email alerts
|

Tracking of Second Primary Melanomas in Vemurafenib-Treated Patients

Abstract: Author Contributions: Dr Chen had full access to all of the data in the study and takes responsibility for the integrity of the data and the accuracy of the data analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 5 publications
8
23
0
Order By: Relevance
“…All of our tested cases expressed pERK and, in accord with prior studies, this finding supports the hypothesis of paradoxical activation of the MAPK pathway by BRAF inhibitor therapy in BRAF wild-type melanocytic lesions. 10,15,16 Similar to our findings, Dalle et al 15 and Goppner et al 16 reported pERK expression in melanomas developed in the setting of BRAF inhibitor therapy. A recent case report of marked resolution of vemurafenib-induced cutaneous lesions upon changing to dual BRAF/MEK combined therapy would be also compatible with these findings.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…All of our tested cases expressed pERK and, in accord with prior studies, this finding supports the hypothesis of paradoxical activation of the MAPK pathway by BRAF inhibitor therapy in BRAF wild-type melanocytic lesions. 10,15,16 Similar to our findings, Dalle et al 15 and Goppner et al 16 reported pERK expression in melanomas developed in the setting of BRAF inhibitor therapy. A recent case report of marked resolution of vemurafenib-induced cutaneous lesions upon changing to dual BRAF/MEK combined therapy would be also compatible with these findings.…”
Section: Discussionsupporting
confidence: 90%
“…[9][10][11]15,17 Based on our study and previous reports that these lesions are predominantly BRAF wild-type and express pERK but not pAKT, we hypothesized that these melanocytic lesions would have distinct histopathologic and immunohistochemical features as a result of paradoxical MAPK pathway activation. In the largest series of 36 melanocytic lesions excised during vemurafenib therapy by Perier-Muzet et al, 17 histopathologic details were not reported.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…15,16 Dalle et al 17 and Haenssle et al 18 have stressed the importance of repeated skin examination, including sequential dermoscopy, for the early detection of subsequent primary melanomas in patients who receive these treatments. Also of interest was our finding that the risk of a subsequent primary invasive melanoma following a first primary in situ melanoma was more than 4 times higher than that in the general population, and only slightly lower than the relative risk following a first primary invasive melanoma.…”
Section: Discussionmentioning
confidence: 99%